Bahasa sebagai Medium Makna : Tinjauan Filsafat Bahasa terhadap Hakikat Bahasa Manusia - Novitasari Novitasari; A. Muh. Taufiq (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Language is a fundamental phenomenon in human life that plays a role not only as a means of communication, but also as a medium for the formation of meaning, thoughts, and social reality. This study aims to analyze the nature of language as a medium of meaning in the perspective of the philosophy of language through the thoughts of the main figures, namely Ferdinand de Saussure, Gottlob Frege, Ludwig Wittgenstein, and J. L. Austin and John Searle. This research uses a qualitative approach with a literature review method, with data sources in the form of classical and contemporary works on the philosophy of language and relevant scientific literature. The analysis is carried out in a descriptive-analytical and reflective-critical manner to uncover the main concepts of language and meaning. The results of the study show that language has a constitutive role in human life. Saussure asserts that meaning is both structural and conventional; Frege shows the cognitive dimension of meaning through the distinction between sense and reference; Wittgenstein views meaning as a use in the context of social practice; while Austin and Searle emphasize the performative power of language as a social action. Thus, language not only represents reality, but also shapes the way humans think, understand, and construct social reality. This study makes a theoretical contribution to the development of the philosophy of language and its relevance in the study of linguistics, education, and the humanities.